2022
DOI: 10.7759/cureus.26751
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Leptin in Systemic Lupus Erythematosus: Is It Still a Mystery?

Abstract: Systemic lupus erythematosus (SLE) is a chronic inflammatory connective tissue disease with varying clinical manifestations. Recent studies have proposed that leptin may be related to SLE development. This study aims to assess current information regarding the relationship between leptin and SLE. A systematic search was done using PubMed, Google Scholar, ScienceDirect, Epistemonikos, and Cochrane Library databases. Studies published in the English language in the last 10 years were selected based on predefined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Numerous studies, including observational studies, clinical trials, and animal experiments have been performed to examine the association between adipokine levels and SLE risk. As mentioned, above however, the existing studies [4][5][6][7][8][9][10][11][12] on the associations between the three major adipokines and SLE have shown inconsistent results; some support null associations while others support significantly correlated relationships. Since the observational studies are usually subject to confounding effects (either unobserved or unadjusted) and reverse causality, especially for retrospective studies, the positive findings of these previous studies should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Numerous studies, including observational studies, clinical trials, and animal experiments have been performed to examine the association between adipokine levels and SLE risk. As mentioned, above however, the existing studies [4][5][6][7][8][9][10][11][12] on the associations between the three major adipokines and SLE have shown inconsistent results; some support null associations while others support significantly correlated relationships. Since the observational studies are usually subject to confounding effects (either unobserved or unadjusted) and reverse causality, especially for retrospective studies, the positive findings of these previous studies should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 98%
“…Leptin levels are highly correlated with adiposity, a commonly known risk factor for a variety of complex diseases such as diabetes, certain cancer types, and cardiovascular disease [3]. To date, observational studies and meta-analyses [4][5][6][7] have shown that compared to healthy controls, serum/plasma leptin levels are elevated in patients with SLE and tend to increase with disease severity. Furthermore, a review article [8] discussed the pathogenic mechanism of leptin in SLE to provide insights into the development of leptin-based approaches for the treatment of SLE.…”
Section: Introductionmentioning
confidence: 99%
“…Leptin is involved in low-grade inflammation due to overweight and obesity and is considered a proinflammatory adipokine [44]. In SLE patients, leptin is highly produced; however, it does not correlate with disease activity [45].…”
Section: Cytokines and Adipokines In Sle Along With Metsmentioning
confidence: 99%
“…р К-У =0,0005 Частота ИР нарастала от 1 (3%) случая при «нормальном весе» до 4 (18%) при «скрытом» и 10 (29%) при «классическом» фенотипе (р=0,009 при сравнении с «нормальным весом»). Продемонстрировано постепенное увеличение доли пациентов, получавших гипотензивные препараты: от 2 (6%) при «нормальном весе» до 10 (45%) при «скрытом» фенотипе (р=0,0012 при сравнении с «нормальным весом») и до 23 В зарубежной и отечественной литературе не найдено сведений о сравнении концентрации лептина при РА и СКВ, хотя существуют сообщения как о повышенных, так и о сходных уровнях адипоцитокина при этих ИВРЗ по сравнению со здоровым контролем [26][27][28][29]. В ряде работ частота ИР при РА оказалась больше, чем при СКВ [33,34], а в других исследованиях она была сопоставима [35,36].…”
Section: а бunclassified
“…Уровень лептина прямо коррелирует с толщиной интимамедиа сонных и кальцификацией коронарных артерий, прогрессированием атеросклероза, СН и тяжелым течением ИБС [19][20][21][22][23][24][25]. Данные об уровне лептина при РА и СКВ, а также о его взаимосвязи с метаболическими нарушениями противоречивы [26][27][28][29].…”
unclassified